Identification and selection of indicators of socio-educational factors that affect the quality of services - Enshaei, Hamed (2020)
Municipalities in Mazandaran province (Iran), like other service organizations, are working within legal frameworks. In light of the increasing importance of customer satisfaction and respect in municipalities, the objective of this article is to identify and evaluate indicators of social factors that affect the quality of educational services. The statistical population of the present study included experts and university professors in the Mazandaran province. 15 people were selected by a non-random sampling method. Based on previous studies, research literature, and interviews conducted, the questionnaire was designed and approved. Of 36 questions on social factors that affect the quality of educational services, 7 were related to the quality of educational services. The examination of the items of the questionnaire was carried out with the Delphi technique approach and the suitability of the components and dimensions was measured using the SPSS software. According to the results of the second round of the Delphi technique, 33 indicators of social factors that affect the quality of educational services and 5 indicators of quality of service obtained a score higher than 3. The educational services based on the criteria proposed by the experts included the behavior of the employees, in addition to their competence and skills, innovation in the provision of educational services, coordination and responsibility of the organization, organizational trust, organizational performance, social responsibility and the labor values of employees. Furthermore, the mean of all dimensions was between 4 and 5 (between appropriate and completely appropriate). In conclusion, there was an adjustment between all dimensions of social factors that affect the quality of educational services according to the proposed criteria.